Suboptimal Attainment of Global Goals of Human Rights, Universal Health Coverage and Sustainable Development Goals in Gaza During 2023–2024 - Alkhaldi M; Akilan B; Hoteit M; Elhadidy M; Morrison S (Risk Management and Healthcare Policy)
Mohammed Alkhaldi,1– 4 Bhavana Akilan,5 Maha Hoteit,6,7 Mohamed Elhadidy,8– 10 Suzanne Morrison11 1Department of Public Health, Faculty of Communication, Arts and Sciences, Canadian University Dubai, Dubai, United Arab Emirates; 2School of Physical and Occupational Therapy, Faculty of Medicine, and Health Sciences, McGill University, Montreal, QC, Canada; 3Centre for Tropical Medicine and Global Health, Nuffield Department of Medicine, The University of Oxford, Oxford, UK; 4The Middle East and North Africa Regional Network, The Global Health Network, Dubai, United Arab Emirates; 5Global Leadership and Health Humanities, University of Toronto Scarborough, Toronto, Ontario, Canada; 6Faculty of Public Health, Lebanese University, Beirut, Lebanon; 7National Council for Scientific Research, Lebanon (CNRS-Lebanon), Beirut, Lebanon; 8Center for Genomics, Helmy Institute for Medical Sciences, Zewail City of Science and Technology, Giza, Egypt; 9Biomedical Sciences Program, University of Science and Technology, Zewail City of Science and Zewail City of Science and Technology, Giza, Egypt; 10Department of Bacteriology, Mycology and Immunology, Faculty of Veterinary, Medicine, Mansoura University, Mansoura, Egypt; 11Department of International Affairs and Social Sciences, College of Humanities and Social Sciences, Zayed University, Abu Dhabi, United Arab EmiratesCorrespondence: Mohammed Alkhaldi, Email mohammed.alkhaldi@mcgill.caAbstract: The Israel military occupation, ongoing for over 75 years, has profoundly impacted the health and well-being of Palestinians. Despite longstanding calls for Universal Health Coverage (UHC) and sustainable development, the response of global health systems and organizations to crises such as the recent large-scale military assault on Gaza in October 2023 has been inadequate. There is a critical need to examine why these global health approaches have failed and how they can be restructured to address the unique challenges in Gaza effectively. This analysis aims to analyze the shortcomings of global health strategies in the context of the Gaza crisis during 2023– 2024, evaluate their alignment with UHC and the Sustainable Development Goals (SDGs), and propose actionable solutions to enhance their relevance and effectiveness in conflict-affected settings. The ongoing military assault has rendered Gaza uninhabitable, exacerbating mass human loss, destruction, health insecurity, and widespread social inequities. The crisis has highlighted the erosion of health systems and the inability to meet basic population needs. Global health strategies, as currently implemented, fail to address the specific challenges of Gaza, including ensuring human rights for health, achieving UHC, and advancing SDGs. These failures are rooted in a lack of context-specific adaptation, inadequate accountability, and unresponsive global health diplomacy. The analysis concludes that global health entities and organizations have been largely ineffective in responding to the Gaza crisis, resulting in significant inequities and failures in life-saving actions. To address these challenges, there is an urgent need to tackle the factors behind the ineffective role of these organizations and suboptimal attainment of global goals. This role of global health should be redefined. Reforming the existing global health architecture and shaping well-representative alliances by involving influential actors from the Global South is a priority. These alliances should prioritize accountability, advocacy, and diplomacy while developing innovative and context-specific approaches to safeguard human rights, achieve UHC, and promote sustainable development in Palestine.Keywords: global health, UHC, SDGs, health rights, Palestine, Gaza